Hydrocarbon prospectively determination of â€œeagle fieldâ€, coastal swamp ii Niger delta. - M T, Olowokere; Hassane, Amadou; M. A, Alonge; E. Ajibade, Adekola (International Journal of Advanced Geosciences, 2019)
Seismic and well log data were collected from onshore depobelt of Nigeria with a total of 1000 seismic lines and 3 wells. The main objective of the study was to determine hydrocarbon prospectivity and reserve estimates of the field. The evaluation centred on seismic interpretation and 3D visualisation (DHI detection) of the â€œEjanla Fieldâ€ 3D in total, Four horizons have been interpreted regionally for correlation purposes and three as prospect specific horizons. Four prospects and some, more speculative leads were identified in the area of which most are conventional three way dip/fault closures and some hanging wall closures. The potential for stratigraphic trapping was also recognized. The study showed that the small closure areas and limited hydrocarbon column lengths affected the number of prospects and at the shallow levels.The main risk to oil prospectivity in the area as revelled by the data interpretation is gas which may have resulted from the observed higher geothermal gradient in the deeper depth. Reservoir development and retention (overpressure) for prospects and leads in the deeper and more distal sedimentological settings form additional risks.Â Â Â Â